Therapeutic Alliance and Treatment Outcome in Cognitive Behavior Therapy for Obsessive-Compulsive Disorder - Wolf, Nadja; Oppen, Patricia van; Hoogendoorn, Adriaan W.; Balkom, Anton J. L. M. van; Visser, Henny A. D. (Frontiers in Psychiatry, 2022)
Objective Therapeutic alliance has consistently been found to predict treatment outcomes across various psychotherapies and patient diagnosis. However, the relationship between therapeutic alliance and outcome in Cognitive Behavioral Therapy (CBT) has shown mixed results. This study investigated the impact of different aspects of therapeutic alliance in CBT for Obsessive-Compulsive Disorder (OCD). Method Data from two previously completed randomized controlled trials of 208 patients with OCD and their therapists were analyzed. Therapeutic alliance was assessed at week 4 of treatment with the patient-rated and therapist-rated Working Alliance Inventory (WAI), which includes three subscales to measure alliance domains (Goal, Task and Bond). Higher WAI score reflects a better therapeutic relationship. OCD severity was rated by independent assessors at baseline and post-treatment using the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS). Linear regression analyses were used to examine the effects of the different aspects of therapeutic alliance on treatment outcome, adjusted for baseline symptom severity. Results A higher total WAI score as rated by therapists significantly predicted a lower post-treatment Y-BOCS. Further, higher scores on the Goal and Task subscales of the WAI were associated with lower post-treatment severity. However, these significant outcomes reflected only small effect sizes. Conclusions In the treatment of OCD, the strength of the therapeutic alliance contributes to outcomes, though to a limited extent. Effective OCD treatment involves the delivery of specific therapy interventions, in the context of a strong therapeutic alliance.